2013
DOI: 10.1007/s00203-013-0894-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and functional analyses of the chitinase-encoding genes in the nematode-trapping fungus Arthrobotrys oligospora

Abstract: Nematode-trapping fungi can secrete many extracellular hydrolytic enzymes such as serine proteases and chitinases to digest and penetrate nematode/egg-cuticles. However, little is known about the structure and function of chitinases in these fungi. In this study, 16 ORFs encoding putative chitinases, which all belong to glycoside hydrolase (GH) family 18, were identified from the Arthrobotrys oligospora genome. Bioinformatics analyses showed that these 16 putative chitinases differ in their functional domains,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…grisea., N. crassa, A. niger, A. nidulans, Mycosphaerella fijiensis, Myc. graminicola and Coccidoides immitis) and basidiomycetes (Postia placenta, Phanerochaete chrysosporium, Laccaria bicolor) are characterized by the presence of only 2-3 ORFs encoding subgroup B chitinases (Seidl et al 2005;Yang et al 2013). …”
Section: Fungal Chitinasesmentioning
confidence: 99%
“…grisea., N. crassa, A. niger, A. nidulans, Mycosphaerella fijiensis, Myc. graminicola and Coccidoides immitis) and basidiomycetes (Postia placenta, Phanerochaete chrysosporium, Laccaria bicolor) are characterized by the presence of only 2-3 ORFs encoding subgroup B chitinases (Seidl et al 2005;Yang et al 2013). …”
Section: Fungal Chitinasesmentioning
confidence: 99%
“…() suggested that chitinases from P. chlamydosporia could also be involved in insect cuticle damage. Other nematophagous fungi, such as A. oligospora , use extracellular enzymes to degrade nematode cuticles (Tunlid and Jansson, ; Yang et al ., ) as well as nematotoxins (Olthof and Estey, ) involved in its trapping nematophagous lifestyle (Nordbring‐Hertz, ). The CAZymes encoded in A. oligospora genome reveal that this fungus not only has kept a complete PCW degradation machinery, but also has a chitinolytic degradation arsenal, though less numerous than the P. chlamydosporia chitin modifying enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted with Trizol Reagent (Invitrogen, Carlsbad, California), purified with a RNeasy Mini Kit (Qiagen, Valencia, Califonia), and then reverse transcribed with PrimeScript RT reagent Kit (Takara, Shiga, Japan) by following the manufacturer’s instructions. RT-PCR was conducted according to our recent report 56 . β-tubulin gene (AOL_s00076g640) of A. oligospora was used as the internal control.…”
Section: Remi Transformationmentioning
confidence: 99%